130 million years of Belum, let's keep it around longer - Abd Razak, Dzulkifli (2008)
WHILE the G8 continues to make more promises on how to save the world, a Malaysian is putting his money where his mouth is. Tan Sri Mustapha Kamal of the wellknown EmKay group took the initiative to launch the Belum Rainforest Research Centre last week. Unveiled by the Sultan of Perak, the centre is poised to be a beacon for sustainability in seeking new solutions to old problems. And why not? Belum is one of the richest biodiversity areas in Malaysia. It lies in Perak, bordering Thailand. Much of its 300,000 hectares of virgin rainforest have been left untouched for over 130 million years, awaiting to be discovered, befitting its name which translates into "the land before time".